(untitled) (London, 2001)
A comprehensive and practical guide providing the technical detail required to upgrade existing water treatment plants to increase processing efficiency and improve overall quality. An invaluable reference for civil engineers
Keywords: Scale jar testing,Flocculated water,Settled water turbidity